The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/jb.187.1.135-142.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dual Transcriptional Control of amfTSBA , Which Regulates the Onset of Cellular Differentiation in Streptomyces griseus

Abstract: The amf gene cluster encodes a probable secretion system for a peptidic morphogen, AmfS, which induces aerial mycelium formation in Streptomyces griseus. Here we examined the transcriptional control mechanism for the promoter preceding amfT (PamfT) directing the transcription of the amfTSBA operon. High-resolution S1 analysis mapped a transcriptional start point at 31 nucleotides upstream of the translational start codon of amfT. Low-resolution analysis showed that PamfT is developmentally regulated in the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…A similar phenomenon occurs in S. coelicolor when the RamS peptide is added to solid cultures of a ramS mutant (52). The observed effect on amfT appears to be characteristic of ClaR and not of AdpA or BldD, which have been described to control amfT expression in S. griseus (44,53), since expression of the gene SCLAV_0719 (bldD) was not affected in S. clavuligerus ⌬claR::aac and SCLAV_1957 (adpA) was upregulated (3.7-fold) only at 60 h of culture.…”
Section: Discussionmentioning
confidence: 77%
“…A similar phenomenon occurs in S. coelicolor when the RamS peptide is added to solid cultures of a ramS mutant (52). The observed effect on amfT appears to be characteristic of ClaR and not of AdpA or BldD, which have been described to control amfT expression in S. griseus (44,53), since expression of the gene SCLAV_0719 (bldD) was not affected in S. clavuligerus ⌬claR::aac and SCLAV_1957 (adpA) was upregulated (3.7-fold) only at 60 h of culture.…”
Section: Discussionmentioning
confidence: 77%
“…For example, in contrast to S. griseus , S. coelicolor BldH does not depend on the bacterial hormone A‐factor for its expression to become derepressed (Takano et al ., 2003). S. griseus contains an orthologue of BldD (Ohnishi et al ., 2008), but, thus far, only one target gene has been identified (Ueda et al ., 2005). In this organism, BldD targets ramCSAB , a gene cluster required for the formation of AmfS, which acts as an extracellular surfactant peptide that stimulates aerial growth.…”
Section: Resultsmentioning
confidence: 99%
“…In this organism, BldD targets ramCSAB , a gene cluster required for the formation of AmfS, which acts as an extracellular surfactant peptide that stimulates aerial growth. In contrast, the orthologous system in S. coelicolor , ramCSAB, encoding the SapB surfactant peptide, is probably not targeted by BldD (Ueda et al ., 2005). We did not identify ramCSAB by ChIP‐chip with BldD, and sequence inspection of its regulatory region revealed no apparent BldD box.…”
Section: Resultsmentioning
confidence: 99%
“…A second important morphogenetic endpoint of the cascade, that seems to bypass bldN and bldM and the production of chaplins, is the five‐gene ramCSABR cluster (= amfTSBAR in S. griseus ) (Chater & Horinouchi, 2003; Ueda et al , 2005; Willey et al , 2006). [There is a paradox in the literature here, since it was reported that a bldM mutant behaved the same as a bldD mutant in the extracellular complementation cascade (Molle & Buttner, 2000); but these experiments may be complicated by the fact that some of the mutants used to define the cascade have different genetic backgrounds.]…”
Section: Genes Implicated In the Regulation Of Formation Of Aerial Hymentioning
confidence: 99%